2017
DOI: 10.1519/jsc.0000000000001613
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Internal Load Indicators and Changes on Intermittent Performance After the Preseason in Professional Soccer Players

Abstract: The aim of this study was to examine the effects of accumulated internal training load (ITL) during the preseason (4 weeks) on changes in the intermittent performance, in a professional soccer team. Twelve professionals soccer players (Mean ± SD age: 27.7 ± 4.3 years; height: 177.1 ± 6.2 cm; body mass: 73.1 ± 5.2 kg; % body fat [Faulkner]: 10.2 ± 1.2) belonging to a Spanish second division team (2013-2014) participated in this study. The 30-15 intermittent fitness test was performed before and after the presea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
6
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 31 publications
8
49
6
5
Order By: Relevance
“…12 that showed a curvilinear dose-response relationship between Banister's TRIMP and individualized TRIMP with changes in maximal aerobic fitness. Our findings are, however, in contrast to those of Campos-Vazquez et al 17 who reported no relationship between HR-derived measures of exercise load and changes in VIFT. It is worth mentioning that basal VIFT level of players in the present study was different from the study of Campos-Vazquez et al 17 (VIFT; 19.0 versus 20.1 km•h -1 ) and consequently it might have influenced the dose-response relationships.…”
Section: **Tables 2 About Here Please ** Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…12 that showed a curvilinear dose-response relationship between Banister's TRIMP and individualized TRIMP with changes in maximal aerobic fitness. Our findings are, however, in contrast to those of Campos-Vazquez et al 17 who reported no relationship between HR-derived measures of exercise load and changes in VIFT. It is worth mentioning that basal VIFT level of players in the present study was different from the study of Campos-Vazquez et al 17 (VIFT; 19.0 versus 20.1 km•h -1 ) and consequently it might have influenced the dose-response relationships.…”
Section: **Tables 2 About Here Please ** Discussioncontrasting
confidence: 99%
“…Our findings are, however, in contrast to those of Campos-Vazquez et al 17 who reported no relationship between HR-derived measures of exercise load and changes in VIFT. It is worth mentioning that basal VIFT level of players in the present study was different from the study of Campos-Vazquez et al 17 (VIFT; 19.0 versus 20.1 km•h -1 ) and consequently it might have influenced the dose-response relationships. The relationship between HR-based training loads and fitness changes in the present study are almost similar or of a lower magnitude than have been previously reported using sRPE 17 or HR-based measures [12][13][14][15][16] .…”
Section: **Tables 2 About Here Please ** Discussioncontrasting
confidence: 99%
See 3 more Smart Citations